Job satisfaction of public sector middle managers in the process of NPM change. Issue 5 (28th May 2017) - Pick, David; Teo, Stephen T. T.
ABSTRACT: This study examines how middle managers in public sector organizations experienced 'New Public Management' (NPM)-related change initiatives. Data from 486 Australian middle managers in state public sector agencies are analysed and the hypothesized model is tested using partial least squares (PLS) structural equations modelling (SEM) on two samples. The cross-validation model analysis brings a new focus on middle managers experience of change via the linkages between the provision of change information, change-induced stressors and the job satisfaction of employees. The 'need for information' is an important element in understanding the consequences of change.